The diagnostic and prognostic implications of silver-binding nucleolar organizer regions in periodontal lesions - Saluja Mini; Vandana K (Wolters Kluwer Medknow Publications, 2008)
Background: The periodontal lesions with cellular proliferation can be assessed by various methods. One of the most recent methods to determine the proliferative activity is silver-staining nucleolar organizer region (AgNOR) staining. The purpose of the present study was to evaluate, if AgNOR count can act as a proliferative marker and can aid in the diagnosis and prognosis of periodontal lesions. Materials and Methods: For this study, subjects with healthy gingival status, non-neoplastic lesions, neoplastic lesions, and plaque-induced gingivitis were included. Following the provisional diagnosis of clinical entity, biopsies were taken from the respective selected sites for histopathological diagnosis. In plaque-induced gingivitis cases, a second biopsy was taken from the selected sites 3 weeks following scaling. After histological confirmation, one more section was prepared, which was subjected to AgNOR staining, and AgNOR numbers were counted by individual and cluster counts and statistically analyzed. Results: Results showed the highest AgNOR count in neoplastic lesions. Non-neoplastic lesions showed a higher AgNOR count as compared to clinically healthy gingiva. Plaque-induced gingivitis showed a considerable reduction in AgNOR count after treatment. Conclusion: Results of this study confirmed that AgNOR count reflects the cellular proliferation and has a limited diagnostic value. However, the prognostic value of AgNOR for periodontal lesions is dependable.